Studi Pengaruh Rekonfigurasi Loop Scheme Terhadap Keandalan Penyulang Blahkiuh dan Penyulang Panglan - yoga, bagus widyananda; Arjana, I Gede Dyana; Pemayun, A.A Gede Maharta (Majalah Ilmiah Teknologi Elektro, 2017)
Abstract —To improve reliability, the do loop system reconfiguration scheme to Blahkiuh feeders and feeders Panglan, by analyzing the calculation SAIFI and SAIDI, can the economy in terms of pressing / kWh minimize the number of unsold losses.   Analysis of calculation results Blahkiuh feeders and feeder reconfiguration Panglan before result Blahkiuh feeder SAIFI 16.534   times/customers/year and the results SAIDI 35.894 hours/customer/year so the numbers of unsold kWh losses from the calculation not save 227,640.841 kWh energy equivalent to Rp 318,718,182.6, while for the results obtained Panglan feeder SAIFI 23.59   times/customer/year, the results of SAIDI 87.39 hours/   customer/year and the calculation results energy not save 238,037.099   kWh equivalent to Rp 364,672,835.7.   After reconfiguration can minimize the number of SAIFI / SAIDI and losses, the results obtained Blahkiuh feeder SAIFI 2,089 times/   customers/year and the results SAIDI of 4.27 hours/customer/year, results energy not save 13369.314 kWh equivalent to Rp 20,481,733.86. For Panglan feeder SAIFI results obtained 1,218 times/customers/year and the results SAIDI 1,242 hours/   customer/year, results energy not save 3880.571 kWh equivalent to Rp 5,945,033.22.   I ntisari — Untuk meningkatkan keandalan maka dilakukan rekonfigurasi sistem  loop scheme  pada penyulang Blahkiuh dan penyulang Panglan, dengan menganalisa perhitungan  SAIFI  dan  SAIDI , ditinjau dari segi ekonomi mampukah menekan/   memperkecil angka kerugian  kWh  yang tidak terjual.   Hasil Analisa perhitungan penyulang Blahkiuh dan penyulang Panglan sebelum rekonfigurasi diperoleh hasil  SAIFI  penyulang Blahkiuh 16,534 kali/pelanggan/tahun dan hasil  SAIDI  35,894 jam/pelanggan/tahun sehingga angka kerugian  kWh  tidak terjual dari hasil perhitungan  energy not save  227.640,841  kWh  setara dengan Rp 318.718.182,6, sedangkan untuk penyulang Panglan diperoleh hasil  SAIFI  23,59 kali/pelanggan/tahun, hasil  SAIDI  87,39 jam/pelanggan/tahun dan hasil perhitungan  energy not save  238.037,099  kWh  setara dengan Rp 364.672.835,7.   Setelah rekonfigurasi dapat memperkecil angka  SAIFI/SAIDI  dan kerugian yang dialami, pada penyulang Blahkiuh didapat hasil  SAIFI  2,089 kali/pelanggan/tahun dan hasil  SAIDI  4,27 jam/pelanggan/tahun, hasil  energy not save  13.369,314  kWh  setara dengan Rp 20.481.733,86. Untuk penyulang Panglan didapat hasil  SAIFI  1,218 kali/pelanggan/tahun dan hasil  SAIDI  1,242 jam/pelanggan/tahun, hasil  energy not save  3.880,571  kWh  setara dengan Rp 5.945.033,22.   Kata Kunci : Sistem  radial ,  Loop scheme ,  SAIFI/SAIDI ,  Energy   not  save [Turnitin Chek 12% 13042017]